KLASIFIKASI MUTU BUAH JAMBU KRISTAL BERDASARKAN BERAT DAN WARNA MENGGUNAKAN LOGIKA FUZZY MAMDANI - Ruri Ridha Rajwari; Raden Arief Setyawan; Muhammad Aziz Muslim (Jurnal Mahasiswa TEUB, 2023)
Crystal guava is a new guava variety that was developed in Taiwan in 1991, then developed in Indonesia in 2009 until now. The advantages of crystal guava lie in its size, taste, and color. In the commercialization of crystal guava fruit, a certain standard is used as a guarantee of crystal guava fruit quality. The quality grade of crystal guava fruit is determined based on severalparameters, including fruit weight and color. Generally, the process of sorting crystal guava fruit is done by utilizing human labor. To sort crystal guava fruit in large quantities, several workers are needed so that all crystal guava fruit can be sorted. The number of workers also affects the speed of the sorting process. In addition, although there are the same standard criteria, the sortingprocess with human labor will be more subjective according to each worker's assessment. Workers' mental and physical conditions, such as fatigue, lack of focus, or others, can affect workers' assessments. Therefore, a decision-2 making system is needed that can work consistently in determining the grade of crystal guava fruit accurately and objectively according to standard criteria with a uniform assessment point of view. In an effort to help run the crystal guava fruit sorting process, a crystal guava fruit quality classification system based on weight and color using mamdani fuzzy logic was developed. Based on the test results, it shows that the applied mamdani fuzzy logic algorithm is able to classify the quality of crystal guava fruit with an accuracy value of 96%. Keywords : Crystal Guava, Quality, Classification, Fuzzy Mamdani